Breastfeeding Rates During the COVID-19 Pandemic in Germany: Data from the CRONOS Registry - Longardt, Ann Carolin; Zöllkau, Janine; Mand, Nadine; Wowretzko, Feline; Büchel, Johanna; Andresen, Kristin; Hoyer, Bimba Franziska; Kraft, Katrina; Pecks, Ulrich; Collaborating authors; Abou-Dakn, Michael; Adler, Jutta; Anders, Sophie-Isabelle; Backes, Clara; Banz-Jansen, Constanze; Berghäuser, Martin; Bohlmann, Michael; Brüggmann, Dörthe; Buchfink, Bettina; Dammer, Ulf; Delius, Maria; Dressler-Steinbach, Iris; Engler-Hauschild, Sarah; Fröhlich, Christiane; Gattung, Luise; Glisic, Lazar; Haeffner, Verena; Hagenbeck, Carsten; Hager, Dietrich; Hain, Renée; Hasmüller, Stephan; Heimann, Yvonne; Hollatz-Galuschki, Elsa; Jakubowski, Peter; Jebens, Anja; Kaup, Lisa; Kohll, Céline; Lastinger, Julia; Manz, Maike; Markfeld-Erol, Filiz; Marquardt, Sabrina; Maul, Holger; Morfeld, Christine; Müller, Thomas; Ozalinskaite, Agne; Redlich, Anke; Richter, Manuela F.; Riebe, Bastian; Ringwald, Friederike; Rohne, Jens; Rühl, Ina; Schäffler, Henning; Schindlbeck, Christian; Schlembach, Dietmar; Schmidt, Saskia; Schneider, Michael; Schrey-Petersen, Susanne; Sczesny, Robert; Seliger, Gregor; Solomon, Diana-Alexandr; Sondern, Kathleen; Stegemann, Carolin; Weide, Johanna; Weigel, Michael; Winkler, Jennifer (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
SARS-CoV-2 infection and COVID-19 disease are thought to have an impact on breastfeeding rate – besides other known peripartal issues. Data of the national CRONOS registry regarding breastfeeding behavior in 6,746 women was analyzed regarding the time window between maternal SARS-CoV-2 infection and time of delivery. In addition, other influencing factors like the predominant viral variant, maternal disease severity, and gestational age at delivery were taken into account. Our data suggest that within the variables analyzed, in the case of acute maternal infection (<14 days before birth), breastfeeding behavior improved with increasing gestational age at birth (p<0.0001), with less severe maternal illness (p<0.0001) and as the pandemic progressed with less virulent viral variants (p=0.01). When adjusting for COVID-19-associated and non-associated factors, rooming-in remains the most important factor positively influencing breastfeeding behavior. With regards to the benefits for mother and infants from breastfeeding, a separation of mother and child even in case of infectious settings should be avoided.
Keywords: breastfeeding; COVID-19; SARS-CoV-2; CRONOS; neonate